THE ASSESSMENT OF AGROPHYSICAL AND AGROCHEMICAL PROPERTIES OF THE DARK BROWN (CHESTNUT) SOIL OF THE SOUTHERN PART OF THE ROSTOV REGION - E. K. Kuvshinova; Yu. V. Gordeeva; Zh. V. Matveykina; E. V. Kravtsova (Зерновое хозяйство России, 2018)
The article deals with the data of several agrophysical and agrochemical properties of the dark brown (chestnut) soil of the southern arable part of the Rostov region. These properties do not only characterize soil fertility, but also promote the growth and development of the plants, influence on their productivity. The awareness of the soil properties in the agrocenosis allows not only estimating its condition but applying the technologies of its improvement. The article considers the analysis of each 0-10 cm soil layer to the one meter depth that gives a clear understanding about the changes of the indexes in the depth. There have been determined the indexes of grain-size and aggregated composition of soil, density of soil, content and reserves of humus, pH and solid residue.